PROBLEMS AND PROSPECTS OF PHARMACEUTICAL PREVENTION IN PROFESSIONAL DISEASES - Андрей Георгиевич Петров; Сергей Николаевич Филимонов; Виктор Андреевич Семенихин; Ольга Владимировна Хорошилова (Медицина в Кузбассе, 2020)
The review is devoted to modern approaches to the problem of pharmaceutical prophylaxis in occupational diseases. The problems of interaction between pharmaceutical workers and representatives of medical organizations in the optimization of pharmaceutical care in the system of pharmaceutical prevention are emphasized. The prospects of introducing pharmaceutical prevention into the treatment of occupational diseases are shown.